সাঁকো ‍(ইণ্টাৰমিডিয়েট কোর্স ইন অসামিস) - (:unkn) unknown (Central Institute of Indian Languages Mysore, 1999)
This is an intermediate course book of Assamese language learners.
Sanko (An Intermediate Course in Assamese)
Keywords: Assamese; Intermediate Course; Assamese